Role of aneuploid circulating tumor cells and CD31+ circulating tumor endothelial cells in predicting and monitoring anti‐angiogenic therapy efficacy in advanced NSCLC. Issue 11 (12th September 2021) - Zhang, Tongmei; Zhang, Lina; Gao, Yuan; Wang, Ying; Liu, Yanxia; Zhang, Hongmei; Wang, Qunhui; Hu, Fanbin; Li, Jie; Tan, Jinjing; Wang, Daisy Dandan; Gires, Olivier; et al.
Abstract : Prognosticating the efficacy of anti‐angiogenic therapy through longitudinal monitoring and early detection of treatment resistance in cancer patients remain highly challenging. In this study, co‐detection and comprehensive phenotypic and karyotypic molecular characterization of aneuploid circulating tumor cells (CTCs) and circulating tumor endothelial cells (CTECs) were conducted on non‐small cell lung cancer (NSCLC) patients receiving bevacizumab plus chemotherapy. Prognostic values of the cell‐based significant univariate risk factors identified by Cox regression analyses were progressively investigated. Subjects showing an increase in total post‐therapeutic platelet endothelial cell adhesion molecule‐1 (CD31) – CTCs and CD31 + CTECs exhibited a significantly reduced median progression‐free survival (mPFS) and overall survival. Further stratification analyses indicated that pretherapeutic patients bearing vimentin (Vim) + CTECs (mesenchymal M‐type) at baseline revealed a significantly shortened mPFS compared with patients with Vim – CTECs. Post‐therapeutic patients harboring epithelial cell adhesion molecule (EpCAM) + CTCs and CTECs (epithelial E‐type), regardless of Vim expression or not, showed a significantly reduced mPFS. Post‐therapeutic patients possessing de novo EpCAM + /Vim + (hybrid E/M‐type) CTECs displayed the shortest mPFS. Patients harboring either pre‐ or post‐therapeutic EpCAM – /Vim – null CTECs (N‐type) exhibited a better response to therapy compared to patients harboring EpCAM + and/or Vim + CTECs. The presented results support the notion that baseline Vim + CTECs and post‐therapeutic EpCAM + CTCs and CTECs are predictive biomarkers for longitudinal monitoring of response to anti‐angiogenesis combination regimens in NSCLC patients. Abstract : Aneuploid CD31 − CTCs and CD31 + CTECs, a pair of mutually related and interacting cellular circulating tumor biomarkers, play a critical role in tumorigenesis, neovascularization, and cancer metastasis. Longitudinally comprehensive co‐detection of diverse subtypes of CTCs and CTECs during therapy by iFISH may effectively prognosticate and real‐time monitor therapeutic efficacy or emerging resistance in cancer patients subjected to anti‐angiogenic combination regimens.